Antibacterial Interventions for Orthodontic Appliances; Surface Modifications, Coatings and Bulk-Incorporated Antibacterial Agents: Materials, Mechanisms and Clinical Application—A Scoping Review - Berta Furió-Alonso; Javier Gil; Danica Nikolic Jovanovic; Andreu Puigdollers-Pérez (Materials, 2026)
Biofilm accumulation on orthodontic appliances is a recognized risk factor for white spot lesion formation and caries during treatment. Antibacterial surface modifications and coating strategies have been proposed as appliance-level preventive approaches. Studied interventions in the literature span true thin-film surface coatings, plasma-based and ion-implantation surface modifications, and bulk-incorporated antibacterial agents in appliance matrix materials. Yet the extent to which in vitro efficacy translates to clinically meaningful protection remains unresolved. This PRISMA-ScR-compliant scoping review searched PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, and Google Scholar, identifying 109 eligible studies: 96 in vitro, 8 in vivo animal studies and 5 clinical trials, covering brackets, archwires, clear aligners, bands, miniscrews, elastomeric ligatures, and removable appliances, some articles studied multiple types of appliances. In vitro studies consistently demonstrated significant reductions in bacterial adhesion and biofilm formation across all appliance types, with silver-based coatings and nitrogen-doped TiO2 showing the broadest evidence base; combination systems (Ag/ZnO, CuO-ZnO) outperformed individual agents. The 13 in vivo and clinical studies provided limited but directionally supportive evidence: silver nanoparticle-incorporated acrylic retainers reduced S. mutans counts in a double-blind RCT, and silver-infiltrated tungsten material-maintained biofilm reduction after simulated two-year abrasion. Coating durability emerged as an important determinant of potential clinical translation. Surface-deposited thin-film coatings degraded substantially within one month of intraoral use, whereas substrate-integrated approaches showed greater longevity. This scoping review maps the current evidence landscape, identifies coating durability and clinical endpoint validation as critical gaps, and prioritizes silver-based and nitrogen-doped TiO2 coatings for future randomized clinical trials.